Peran Majelis Ulama Indonesia Dalam Mitigasi Pandemi Covid-19 (Tinjauan Tindakan Sosial dan Dominasi Kekuasaan Max Weber) - Muhamad Agus Mushodiq; Ali Imron (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis paper aims to uncover the motives of the Indonesian Ulema Council (MUI) in issuing Muslim community religious edicts during the COVID-19 Pandemic. In exploring this motive, the writer uses the theory of social action and power domination initiated by Max Weber. This type of research is qualitative research, researchers do the description and interpretation of data from primary sources taken from the official MUI website and other data that supports the results of the study. The results of this paper are: First, MUI is an actor of social religious action. Second, the motives for MUI socio-religious actions through fatwas issued contain three dominant motives. Third, the instrumentally rational motives in the fatwa refer to various models of worship. Fourth, MUI uses the values of the Islamic Religion which originate from the Qur'an, Hadith, and Jurisprudence. Fifth, MUI seeks to continue the traditions of the Prophets and Friends. Sixth, the MUI's Domination of Power determines the mandatory and unlawful matters in worship. Seventh, the MUI has a very important role in the mitigation effort of the COVID-19 Pandemic.Keywords: Social Actions; Power Domination; COVID-19; Mitigation, MUI Fatwa. AbstrakTulisan ini bertujuan untuk mengungkap motif-motif Majelis Ulama Indonesia (MUI) dalam menerbitkan fatwa peribadatan masyarakat muslim saat Pandemi COVID-19. Dalam mengeksplorasi motif tersebut, penulis menggunakan teori tindakan sosial dan dominasi kekuasaan yang digagas oleh Max Weber. Jenis penelitian yang digunakan adalah penelitian kualitatif, peneliti melakukan deskripsi dan interpretasi data dari sumber primer yang diambil dari situs resmi MUI dan data lain yang mendukung hasil penelitian. Adapun hasil dari tulisan ini adalah: Pertama, MUI merupakan aktor dari tindakan sosial keagamaan. Kedua, motif tindakan sosial keagamaan MUI melalui fatwa yang diterbitkan mengandung tiga motif dominan. Ketiga, motif instrumentally rational dalam fatwa mengacu pada berbagai macam model peribadatan. Keempat, MUI menggunakan nilai-nilai dari Agama Islam yang bersumber dari Alquran, Hadis, dan Kaidah Fikih. Kelima, MUI berupaya untuk meneruskan tradisi para Nabi dan Sahabat. Keenam, Dominasi Kekuasaan MUI penentu hal wajib dan haram dalam peribadatan. Ketujuh, MUI sangat penting perannya dalam upaya mitigasi Pandemi COVID-19.Kata Kunci: Tindakan Sosial; Dominasi Kekuasaan; COVID-19; Mitigasi, Fatwa MUI.